2010
DOI: 10.1093/molbev/msq137
|View full text |Cite
|
Sign up to set email alerts
|

Phylodynamic Analyses of Rotavirus Genotypes G9 and G12 Underscore Their Potential for Swift Global Spread

Abstract: Rotaviruses (RVs) are responsible for more than 600,000 child deaths each year. The worldwide introduction of two life oral vaccines RotaTeq and Rotarix is believed to reduce this number significantly. Before the licensing of both vaccines, two new genotypes, G9 and G12, emerged in the human population and were able to spread across the entire globe in a very short time span. To quantify the VP7 mutation rates of these G9 and G12 genotypes and to estimate their most recent common ancestors, we used a Bayesian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
281
2
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(299 citation statements)
references
References 38 publications
11
281
2
5
Order By: Relevance
“…The introduction of RV vaccines may result in additional selective pressure on circulating RV strains and may affect their rates of evolution (20). If vaccine-induced selective pressure against G9 strains is lacking, this could facilitate the rapid global spread of G9 strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of RV vaccines may result in additional selective pressure on circulating RV strains and may affect their rates of evolution (20). If vaccine-induced selective pressure against G9 strains is lacking, this could facilitate the rapid global spread of G9 strains.…”
Section: Discussionmentioning
confidence: 99%
“…G5 and P[7] are historically considered the most prevalent G and P RVA genotypes in swine, respectively (18). However, recent studies have shown that RVA G9 and G12 genotypes are emerging worldwide in humans and swine (2,(19)(20)(21)(22)(23). …”
mentioning
confidence: 99%
“…In addition, several G-genotypes (G5, G6, G8, G10, G11 and G20) and Pgenotypes (Ben Hadj Fredj et al, 2013b;Gautam et al, 2015;Gentsch et al, 2005;Santos & Hoshino, 2005;Solberg et al, 2009;Tacharoenmuang et al, 2015). At least 73 G/P-genotype combinations of RVAs infecting humans have been described (Matthijnssens et al, 2009 (B anyai et al, 2012;Gómez et al, 2014;Matthijnssens et al, 2010;Rahman et al, 2007;Santos & Hoshino, 2005;Stupka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, some specific G and P genotypes are dominant in individual animal species. In human RVAs, G genotypes G1-G4, G9 and G12, and P genotypes P[4], P [6] and P [8] are considered as major genotypes, whilst porcine RVAs are assigned mostly to G genotypes G3-G5, G9 and G11, and P genotypes P [6], P [7] and P [13] (Santos & Hoshino, 2005;Martella et al, 2010Matthijnssens et al, 2010. Recently, a classification system based on the genetic characterization of all 11 gene segments has been proposed for RVAs with the aim of facilitating tracing of the origin and evolution of RVAs (Matthijnssens et al, 2008).…”
mentioning
confidence: 99%